Formylated honokiol analogs showed antitumor activity against lung carcinoma. Issue 8 (September 2019) - Deng, Senyi; Zhang, ChuanFen; Yang, Lina; Ma, Liang
Abstract : Honokiol, a biphenolic neolignan with inappreciable toxicity isolated from Magnolia officinalis, has been reported to have antiangiogenic and antitumor properties in several tumor cell lines and tumor xenograft models. In our previous study, structural modification by chemical synthesis has been carried out to develop novel honokiol derivatives to improve antitumor activity and clarify the structure–activity relationship. Honokiol analogs, especially 3, 5′-diformylated honokiol HK-(CHO)2, have been found to moderately block the newly grown segmental vessels from the dorsal aorta in the transgenic zebrafish-based assay, show antiangiogenic property, and exert medium cytotoxicity against two lung cell lines (Lewis lung carcinoma LL/2 cells and human non-small-cell lung cancer A549 cells). However, the in-vitro and in-vivo antitumor effects of formylated honokiol derivatives against lung carcinoma remained poorly understood. In the study, two formylated honokiol derivatives also showed potent antitumor effects in the Lewis lung carcinoma cells, K-ras G12D -dirived lung adenocarcinoma mice, and a mouse lung tumor xenograft model, with HK-(CHO)2 being most efficacious. The potential mechanism was inhibiting cell proliferation and inducing apoptosis in lung cancer by the regulation of vascular endothelial growth factor A expression. These results further suggested that HK-(CHO)2 might be potential candidates for the treatment of lung carcinoma. Abstract : Supplemental Digital Content is available in the text.